Pyrosequencing the transcriptome of the greenhouse whitefly, Trialeurodes vaporariorum reveals multiple transcripts encoding insecticide targets and detoxifying enzymes - Karatolos, Nikos (BioMed Central, 2011)
BACKGROUND: The whitefly Trialeurodes vaporariorum is an economically important crop pest in temperate regions that has developed resistance to most classes of insecticides. However, the molecular mechanisms underlying resistance have not been characterised and, to date, progress has been hampered by a lack of nucleotide sequence data for this species. Here, we use pyrosequencing on the Roche 454-FLX platform to produce a substantial and annotated EST dataset. This 'unigene set' will form a critical reference point for quantitation of over-expressed messages via digital transcriptomics. RESULTS: Pyrosequencing produced around a million sequencing reads that assembled into 54,748 contigs, with an average length of 965 bp, representing a dramatic expansion of existing cDNA sequences available for T. vaporariorum (only 43 entries in GenBank at the time of this publication). BLAST searching of non-redundant databases returned 20,333 significant matches and those gene families potentially encoding gene products involved in insecticide resistance were manually curated and annotated. These include, enzymes potentially involved in the detoxification of xenobiotics and those encoding the targets of the major chemical classes of insecticides. A total of 57 P450s, 17 GSTs and 27 CCEs were identified along with 30 contigs encoding the target proteins of six different insecticide classes. CONCLUSION: Here, we have developed new transcriptomic resources for T. vaporariorum. These include a substantial and annotated EST dataset that will serve the community studying this important crop pest and will elucidate further the molecular mechanisms underlying insecticide resistance.